Uncountable Skin Lesions in a Mentally Disabled Patient: A Quiz - Iwona Chlebicka; Aleksandra Stefaniak; Karolina Wójcicka; Jacek C. Szepietowski (Medical Journals Sweden, 2020)
Abstract is missing (Quiz)